Reconceptualizing and describing teachers’ knowledge of language for content and language integrated learning (CLIL) - Morton, Tom (International Journal of Bilingual Education and Bilingualism, 2018)
Content and language integrated learning (CLIL) is an approach to bilingual education in which academic content and an additional language are taught at the same time. It is growing rapidly throughout the world, with the medium of instruction in most CLIL classrooms being English. This means that many teachers around the world are teaching academic content in English, which is neither their, nor their students’, first language. There is thus a need to establish and clarify the knowledge of language necessary for these teachers to carry out teaching tasks effectively. Drawing on [Ball, Deborah Loewenberg, Mark Hoover Thames, and Geoffrey Phelps. 2008. “Content Knowledge for Teaching: What Makes It Special?” Journal of Teacher Education 59: 389–407.] work on content knowledge for teaching (as do [Freeman, Donald, Anne Katz, Pablo García Gómez, and Anne Burns. 2015. “English-for-Teaching: Rethinking Teacher Proficiency in the Classroom.” ELT Journal 69 (2): 129–139.] in the ELT context), the article proposes the construct of ‘Language knowledge for content teaching’ (LKCT). This construct has two sub-domains: common language knowledge for content teaching (CLK-CT) and specialized language knowledge for content teaching (SLK-CT). These sub-domains are described and illustrative examples from a corpus of classroom interactions are presented. It is suggested that further research can develop these domains of teacher's’ language knowledge for CLIL both theoretically and empirically, and they are offered as a tool for mapping out the language component of the knowledge base for CLIL teacher education.
Keywords: Content and Language Integrated Learning (CLIL); English-medium instruction (EMI); teachers’ knowledge; language knowledge for content teaching (LKCT); Scopus; JCR